Mutual Transformation of Flux-Controlled and Charge-Controlled Memristors - Dalibor Biolek; Zdenik Kohl; Jiri Vavra; Viera Biolkova; Kapil Bhardwaj; Mayank Srivastava (IEEE Access, 2022)
Two-ports for mutual transformation between flux-controlled memristors and charge-controlled memristors are proposed. Attention is paid to memristors with the region of negative differential memristance in the charge-flux constitutive relation, when such a transformation should be made carefully. Connections between this transformation, duality rules, and Chua’s table of higher-order elements are described. The proposed transforming cells can be made up of commercially available integrated circuits. Their proper operation is demonstrated via simulations and lab experiments with memristive oscillators.